Suprachoroidal Versus Intravitreal Injection of Triamcinolone Acetonide As Primary Treatment For Diabetic Macular Edema - Khan, Fatima Shafqat; Asghar, Asfandyar; Intisar-ul-haq , Brig Rana; Nazir, Tehmina; Obaid , Naila; Aslam, Munazza (Journal of Rawalpindi Medical College, 2023)
Objective: This study aims to evaluate and compare the effects of suprachoroidal and intravitreal triamcinolone administration, as a primary treatment, on best corrected visual acuity (BCVA), central macular thickness (CMT), and intraocular pressure (IOP) in patients with diabetic macular edema (DME). Methods: A quasi-experimental study was conducted from November 2022 to April 2023. 64 eyes were enrolled with Inclusion criteria comprising patients with diabetic macular edema (DME) (central involving) with BCVA < 6/9, CMT > 300 µm on optical coherence tomography (OCT), and no prior DME treatment. Patients were divided into suprachoroidal triamcinolone (SCTA) (Group I) and intravitreal triamcinolone (IVTA) (Group II) groups. Follow-up occurred at 1 week, 1 month, and 3 months post-injection. BCVA, CMT, and IOP were recorded. Data were analyzed using SPSS with a significance threshold of p < 0.05. Results: Both treatment groups exhibited improved BCVA and reduced CMT. Suprachoroidal delivery demonstrated more substantial visual acuity improvements compared to the intravitreal group. Reduction in IOP was observed in the suprachoroidal group at 1stweek post-treatment (p<0.001), while the intravitreal group experienced increased IOP at later follow-ups (p<0.001). Conclusion: This study illuminates the efficacy of both suprachoroidal and intravitreal triamcinolone administration as the primary treatment for DME. While both modalities displayed promising outcomes, suprachoroidal delivery exhibited more substantial visual acuity improvements with fewer side effects and promising alternatives for DME treatment. Keywords: Macular Edema, Intravitreal, Triamcinolone Acetonide, Suprachoroidal, Visual Acuity, Intraocular Pressure.